2013
DOI: 10.1007/s12013-013-9600-1
|View full text |Cite
|
Sign up to set email alerts
|

A Resting-State Functional Magnetic Resonance Imaging Study of Acute Carbon Monoxide Poisoning in Humans

Abstract: The objective of this study was to evaluate the brain function characteristics of carbon monoxide poisoning patients using resting-state functional magnetic resonance imaging (fMRI) method. For this purpose, 12 carbon monoxide poisoning patients and healthy controls were subjected to resting-state fMRI scans separately. A regional homogeneity (ReHo) approach was used to analyze the brain function in carbon monoxide poisoning patients. Compared with control group, the value of ReHo in carbon monoxide poisoning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…In the present experiment, we focused on brain functional changes in children with CO intoxication, but previous studies have shown that adult and pediatric patients with CO intoxication are not identical in terms of brain injury and clinical prognosis. Liu et al found reduced homogeneity (ReHo) in the frontal, insula, occipital, temporal, and cerebellar regions of patients in an fMRI study after CO intoxication in adults, 9 and although our study also found impaired nodal topological properties in the frontal nodes of the affected children, we also found impaired nodal topological properties in the basal ganglia region of the affected children, which was not found in that study. We speculate that it may be related to the fact that the middle cerebral artery in children is much less responsive to hypercapnia than in adults, 37 resulting in reduced cerebrovascular reserve in children and thus more pronounced clinical symptoms in adolescents 38 .…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In the present experiment, we focused on brain functional changes in children with CO intoxication, but previous studies have shown that adult and pediatric patients with CO intoxication are not identical in terms of brain injury and clinical prognosis. Liu et al found reduced homogeneity (ReHo) in the frontal, insula, occipital, temporal, and cerebellar regions of patients in an fMRI study after CO intoxication in adults, 9 and although our study also found impaired nodal topological properties in the frontal nodes of the affected children, we also found impaired nodal topological properties in the basal ganglia region of the affected children, which was not found in that study. We speculate that it may be related to the fact that the middle cerebral artery in children is much less responsive to hypercapnia than in adults, 37 resulting in reduced cerebrovascular reserve in children and thus more pronounced clinical symptoms in adolescents 38 .…”
Section: Discussioncontrasting
confidence: 95%
“…The case group of this study was patients with CO poisoning admitted to the emergency department of our hospital from December 2020 to March 2021. Inclusion criteria 9 : 1) under the age of 18; 2) a history of CO exposure; 3) signs and symptoms of central nervous system injury after poisoning; 4) blood COHb level consistent with the national diagnostic criteria. Exclusion criteria: 1) over the age of 18; 2) excessive head movement during MRI scans (more than 2 mm or 2° in any direction); 3) history of serious neurological or psychiatric illness; 4) history of severe head trauma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more studies have been conducted on delayed encephalopathy following acute CO poisoning ( Hou et al, 2013 ; Lee et al, 2018 ; Wu et al, 2020a , b ), in which the main pathological changes are extensive demyelination of the brain’s white matter, bilateral symmetrical pallidocyte ischemia, and necrosis. There are only a few studies on brain function alterations during the acute phase of CO poisoning ( Dinghua et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Both the acute effects and the treatment protocols of CO poisoning have well-elaborated literature, along with the description of long-term neuropsychiatric and cardiac sequelae. On the other hand, the literature on resting-state functional MRI (rs-fMRI) abnormalities in CO intoxication is rather modest, 4,5 and this is particularly true regarding the studies of the underaged population, where the rapidly developing brain possibly voids the general findings based on adult samples and limits our comprehensive understanding of the disease.…”
mentioning
confidence: 99%